Infection and wound breakdown in spontaneous second‐degree perineal tears: An exploratory mixed methods study. Issue 1 (22nd August 2018) - Wiseman, Octavia; Rafferty, Anne M.; Stockley, Jane; Murrells, Trevor; Bick, Debra
Abstract: Background: Perineal trauma affects large numbers of women who have a vaginal birth. This study explores the incidence, etiology and women's experiences of wound infection/breakdown associated with spontaneous second degree tears. Methods: This was an exploratory mixed methods study set in an urban tertiary National Health Service hospital in 2014‐2015. The study included a prospective observational study of second‐degree tears using electronic patient records. Infection was defined using criteria adapted from Public Health England's Surgical Site Infection Surveillance Service. We also did a case‐control study of maternity records to explore factors associated with perineal infection/wound breakdown, and semi‐structured interviews with a purposeful sample of women who experienced wound infection/breakdown. Results: Of 2892 vaginal births during the study period, 76.8% sustained perineal trauma, with second‐degree tears most commonly recorded (n = 828/28.6%). Sixteen (1.9%) had a documented infection/wound breakdown which were associated with "compromised wound status" (increased severity of wound/poor suturing; P = 0.033) Women complained of a lack of information about their perineum and poor postnatal surveillance by midwives and physicians. Diagnosis and treatment were often delayed by clinicians' reliance on external signs of wound infection. Although the sample size was small, there were no differences in rates of infection between sutured and unsutured second‐degree tears. Conclusions: Although second‐degree tears were common after vaginal birth, wound infection/breakdown was relatively uncommon. Women who report feeling unwell or develop pyrexia postnatally should be assessed urgently. A prospective longitudinal study exploring the long‐term sequelae of second‐degree tears is needed.